(untitled) (Third Sector Social Economic Review, 2022)
In this study, it is aimed to examine the effect of brand awareness and brand experience on brand satisfaction and brand loyalty. A quantitative research was employed on 138 Private Hospital employees in Ankara. Measurement instruments that were previously tested for reliability and validity were used. Correlation and series of regression analyses were applied for investigating relationships and testing research hypotheses. According to the correlation analysis, there are significant positive correlations between brand awareness, brand experience, brand satisfaction, and brand loyalty. As a result of regression analyses, brand awareness and brand experience have a meaningful effect on brand satisfaction and brand loyalty. To test the mediation effect, the four-step procedure proposed by Baron and Kenny (1986) was performed. Research findings show that the effect of brand awareness is partially mediated by brand experience on brand satisfaction and brand loyalty variables.